Dissolution Characteristics of Hydrophobically Associating Polyacrylamide in Stirred Tanks - 周国忠 谢明辉 刘敏 吴华晓 龙湘犁 虞培清 (Chinese journal of chemical engineering, 2010)
Enhanced oil recovery（EOR）by means of polymer flooding is an important technology for the strategic development of offshore oilfields in China.Hydrophobically associating polyacrylamide（HAPAM）has been recently proposed as a new flooding agent.The solubility of HAPAM is low,which is the bottleneck for further improving the oil recovery through polymer flooding in offshore oilfield.Stirred tanks have been used on offshore platforms to enhance HAPAM dissolving.But there is little literature on the study of HAPAM dissolving characteristics in stirred tanks.In this paper,effects of temperature,salinity,stirring speed,impeller type and stirring method on the dissolution of HAPAM are reported.The experimental results manifest that the dissolving rate of HAPAM increases with temperature and stirring speed,but the viscosity of the polymer solution decreases.There is an optimal range of salinity for polymer dissolving.Combining the operation mode of up-pumping with varying stirring speed,hydrofoil impeller can accelerate the dissolution of HAPAM and maintain a high solution viscosity.